Valbenazine for the Treatment of Adults with Tardive Dyskinesia - Harshit Gupta; Alycee R. Moity; Allison Jumonville; Sarah Kaufman; Amber N. Edinoff; Alan D. Kaye (Health Psychology Research)
# Purpose of review